2017
DOI: 10.1097/j.pain.0000000000001051
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis constituent synergy in a mouse neuropathic pain model

Abstract: Cannabis and its psychoactive constituent Δ9-tetrahydrocannabinol (THC) have efficacy against neuropathic pain, however, this is hampered by their side effects. It has been suggested that co-administration with another major constituent cannabidiol (CBD) might enhance the analgesic actions of THC and minimise its deleterious side effects. We examined the basis for this phytocannabinoid interaction in a mouse chronic constriction injury (CCI) model of neuropathic pain. Acute systemic administration of THC dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 39 publications
4
67
0
Order By: Relevance
“…Cannabidiol is the primary non-psychoactive component of Cannabis sativa and has anti-inflammatory, neuroprotective, anxiolytic, and anti-psychotic actions, but does not produce the typical cannabinoid side effects [ 12 , 14 ]. While the actions of THC are at least partly mediated by CB1 and CB2 receptors, the actions of cannabidiol are only partly mediated by CB2 receptors, with other receptor systems having a major role in its activity [ 10 , 15 ].…”
Section: Cannabismentioning
confidence: 99%
See 2 more Smart Citations
“…Cannabidiol is the primary non-psychoactive component of Cannabis sativa and has anti-inflammatory, neuroprotective, anxiolytic, and anti-psychotic actions, but does not produce the typical cannabinoid side effects [ 12 , 14 ]. While the actions of THC are at least partly mediated by CB1 and CB2 receptors, the actions of cannabidiol are only partly mediated by CB2 receptors, with other receptor systems having a major role in its activity [ 10 , 15 ].…”
Section: Cannabismentioning
confidence: 99%
“…THC has been shown to abolish the mechanical and thermal allodynia associated with various neuropathic pain models in rodents [ 15 , 37 , 38 , 39 , 40 ]. However, in addition to analgesia, THC also produces classic cannabinoid side effects such as sedation, catalepsy, reduced locomotion, and hypothermia [ 21 , 24 , 26 , 41 ].…”
Section: How Does This Correlate To Preclinical Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have revealed great complexity in the interaction, with CBD synergistically enhancing or inhibiting the effects of D 9 -THC dependent on the measured variable and the frequency of dosing. [7][8][9][10] It has also been hypothesised that the varying effects of different cannabis chemovars might be due to variation in their terpene content, which can reach concentrations of 3.5% and 10% in flower and trichomes, respectively. [11][12][13] However, few studies have addressed this hypothesis; thus, the present study sought to advance the evidence base on potential terpenoid-cannabinoid interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis sativa, a plant known more commonly as marijuana, has become widely popular due to its induced psychological and euphoric states in an individual who ingests or smokes the plant. More interestingly, the cannabinoids that cause these desired effects also have potential health applications which have been seen to improve a variety of symptoms such as neuropathic pain, seizures, social defects, brain damage from stroke, and lung function in inflammatory lung disease [1][2][3][4][5][6][7][8]. The most popularly used compounds recreationally and therapeutically, Cannabidiol (CBD) and trans-Δ⁹-tetrahydrocannabinol (THC) (Figure 1), are classified as phytocannabinoids since they naturally occur from the Cannabis plant [9].…”
Section: Introductionmentioning
confidence: 99%